ADVERTISING DESIGN FOR ACCESS STUDIO - Aziz, Ahmad Abzal (Arty: Jurnal Seni Rupa, 2020)
Access Architect is an architectural design studio in Semarang, which was founded in 2016. As a company that is still relatively new, Access Architect faces competition from companies that have been engaged in this field before. But there is no promotional media with visual standardization that supports building and enchancing company image. On the other hand, the presence of promotional media is important because it directly relates to clients and remembers Access Architect as a company that is still relatively new. The design of promotional media created for Access Architect includes company profile and portfolio catalog, corporate identity applications, animated videos, and slider website. The manufacturing process is done by manual and digital techniques using Corel Draw and Adobe After Effects applications. The process of designing this promotional media goes through several stages of the work process, namely the preliminary process, pre-production process, the production process, and the post-production process. With the design of promotional media it is expected to help introduce Access Architect in the community, expand the marketing area, and improve the image of the company in order to compete with the competitors.